Clay Mineralogical Studies in Relation to Soil Development And Vegetation in Haldwani Forest Division of Uttar Pradesh - Samra, J. S. (Indian Forester, 1982)
Presence of kaolinite in significant amounts, hydrated axides of Iron, comparatively high organic carbon in lower layers, absence of 14 7 and 4.7Â° A peaks of chlorite and vermiculite and degraded nature of illite in the soils of Naghan and Gunio Rao compartments, qualifies them to represent compuatively more weathered soil sequences. Syzygium cumini indicating relatively moist regime and hence probably more intense weathering have been found to be natural associate of Shoreo robusta in comparatively more weathered soils. Significant amount of blite with smal; quantities of chlorite and vermiculite in the clay fraction of Guliapani and Sunmanthapia compartments having mainly Shorea robusta in the upper storey with non-exacting species like Mallotus philipensis in the second storey, shrub and ground , layer, suggest that soils of these sites are comparatively less weathered representing young sequences and more fertile sites.